Development of piezoelectric micro-energy harvesting system using voltage doubler - Mostafa, Mohammad Golam; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn; Rahman, Towfikur (2015)
Nowadays renewable micro-energy harvesting system is becoming attractive, because this energy is free which leads to reduce energy cost. Piezoelectric is one of the common energy harvesting systems. Generally, the output of a piezoelectric transducer is a small AC voltage and its power is also small. As a result, the convertion of this low AC voltage into DC voltage by using rectifier diode is not suitable since a cut-in voltage drop redues the output voltage as well as power of the system. A micro-energy harvesting interface circuit has been developed by using voltage doubler to improve the performace. The design is a modified model of buck boost converter. In this technique, at first the input voltage is incresed by a voltage double then it is used into a buck boost converter. A diode and a single capacitor have been used in this design instead of bridge rectifier which overcomes the diode conduction losses. 3.4V DC accros a load 1kΩ is obtained when the output voltage of the piezoelectric transducer is 0.54V AC. The circuit has been simulated by using PSpice (V16.5) electronic circuit simulation software and maximum power dissipation 57mW is obtained at the load which is supposed to be better compared to other conventional designs.